Americas in 1994 : a time for leadership (Inter-American Dialogue WashingtonUS, 1994)
Focuses on key issues such as setting the groundwork for a hemisphere linked by free trade and economic partnership, and strengthening the capacity of the Organization of the American states and other institutions for inter-American cooperation, particularly to safeguard democracy and human rights.
DC